Gradual opening of the siphonal tube in an orthoconic cephalopod from the Silurian of Central Bohemia (Czech Republic) - Kolebaba,I. (Journal of the Czech Geological Society, 1999)
A specimen of an orthoconic cephalopod from the Silurian (Ludlow, Ludfordian), Kopanina Formation of Central Bohemia, described by Barrande (1870) as Orthoceras obelus, has been studied in detail. New information was obtained on the morphology of the sipho-cameral structures; the gradual opening of the siphonal tube, enabling the tissue to enter the gas chambers during the ontogeny, has been found out. The specimen was established the holotype of a new species Nucleoceras hollandi sp. n., and was, based on the proved presence of the cameral mantle, attributed to the Family Lamellorthoceratidae Teichert, 1961, Order Pallioceratida Marek, 1998.
Keywords: Mollusca; Cephalopoda; Pallioceratida; functional morphology; internal structures; new taxon; Silurian; Barrandian Area; Bohemia